The Human Immunodeficiency Virus - a Review of the clinical aspects and detection of the infection - Martyna Choinka; Agata Konopka; Natalia Wdowiak; Zuzanna Szczepaniak; Jakub Kalisiak; Anna Szpernalowska; Vimbisoyashe Ivy Matshaba; Karolina Mrugała (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Currently, many people are infected with the human immunodeficiency virus (HIV). Transmission is primarily through sexual contact, with additional routes including mother-infant exposure to needles and needle sharing. Since the HIV/AIDS pandemic was first identified in 1981, more than 75 million people have been infected. Numerous new cases continue to be reported, and infection can become the starting point for the development of HIV. Clinical manifestations include acute retroviral syndrome, opportunistic infections, and dermatological, neuromuscular, and other complications. Despite advances in antiretroviral therapy (ART), challenges remain, including drug resistance, opportunistic infections, and persistent HIV reservoirs in some cell types. Early and accurate diagnosis is essential, and recommended testing protocols include fourth-generation serological tests and point-of-care (POC) testing. ART, which includes combinations of antiretroviral drugs, is the standard treatment, and ongoing research into gene therapy shows promise for the future.   Purpose of the work: The aim of this study is to review and characterize the clinical aspects and detection of human immunodeficiency virus infection.   Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the searchterms encompassing the following keywords: HIV,  human immunodeficiency virus, ART, HIV manifestation, HIV detection, HIV diagnosis, HIV treatment.